Teaching vocabulary : preschool teachers' preparation and delivery in Matu Daro, Mukah/ Paulinus Anak Johie - Anak Johie, Paulinus (2013)
In previous years, vocabulary teaching was neglected by language teachers because it is considered as an add-on to grammar. How ever, in recent years, it is seen as an important aspect for a child's development though it may seem challenging when the students are young. Good vocabulary teaching skills are an invaluable set of tools for teachers of any level. Hence, this study was designed to investigate the methods employed by pre-school teachers to prepare and present their lesson to promote the acquisition of vocabulary meaning. Their reasons for using the techniques are also taken into account. The combination of Cummin's (1981) language and content activities model with Nation (2008) vocabulary teaching strategy were used as framework for the study. In order to collect data, a total of 10 pre-school teachers of various teaching experience in Matu Daro were observed and interviewed. The interview was primarily to elicit how they prepared for their lesson whereas interview [part 2] was used to support classroom observation. The data were analyzed descriptively. Findings revealed that there were a variety of ways in which the teacher prepared and delivered their lesson to promote English vocabulary among pre-schoolers. Their most common way of preparation was by referring to the National Standard Pre-school Syllabus. Others referred to activity books, searched the internet, developed own teaching aids, used MOE teaching aids and BPG Teacher's Handbook. In lesson presentation, the teachers also used several techniques to introduce the words and its meaning. The techniques employed were through the used of pictures, translation, real objects, ICT integration, tells story, song and questioning.In addition, the teachers* reasons were also discussed to support and confirm the results obtained.